BIOKIMIA PENAMBATAN NITROGEN OLEH BAKTERI NON SIMBIOTIK - Danapriatna, Nana (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2010)
Some microbes in the group non-symbiotic bacteria capable of fix nitrogen. The process of nitrogen fixation by non-symbiotic bacteria requires several conditions : (1) the enzyme nitrogense, (2) the availability of energy resources in the form of ATP, (3) the potential lowering of the electron source, (4) a system of protection of nitrogenase enzyme from inactivation by oxygen, and (5) rapid transfer of nitrogen to prevent the inhibition of the enzyme nitrogenase. The result of nitrogen fixation by non-symbiotic aerobic bacteria was higher than the non-symbiotic fixation by anaerobic bacteria. The mechanism of protection of nitrogenase from oxygen by non-symbiotic aerobic bacteria are consuming excessive O2 for respiration and Azotobacter which have a capsule mucus (EPS) a thick helping protect the enzyme nitrogenase from O2. For anaerobic bacteria oxygen is not a problem because the environmental of bacteria are low oxygen